Hepatitis B virus vaccination‐related seroprevalence among health‐care personnel in a Japanese tertiary medical center. Issue 13 (5th April 2016) - Yanase, Mikio; Murata, Kazumoto; Mikami, Shintaro; Nozaki, Yuichi; Masaki, Naohiko; Mizokami, Masashi
Abstract : Aim : Few studies concerning the protective management of hepatitis B virus (HBV) infection among health‐care personnel (HCP), excluding occult HBV or carriers, have been reported. Therefore, we undertook a cross‐sectional study of the updated status of HBV vaccine management by measuring the antibody to hepatitis B surface antigen (anti‐HBs) along with the antibody to hepatitis B core antigen (anti‐HBc). Methods : Both anti‐HBs and anti‐HBc were assessed in 1085 HCP employed by our institute. Hepatitis B virus vaccination‐related histories were recorded using self‐administered questionnaires. Results : Of 1085 HCP, 27 (2.5%) were positive for anti‐HBc, and its positive rate increased with age. Of the 1058 subjects with negative anti‐HBc, 879 (83.1%) were positive for anti‐HBs. The median titer of anti‐HBs was 71.1 mIU/mL, which was higher in female subjects ( P  = 0.037). By age group, the positive rate of anti‐HBs were 77.5%, 89.3%, 90.8%, and 81.6% in the groups aged ≤29, 30–39, 40–49, and ≥50 years, respectively ( P  < 0.001). Of the 908 subjects who reported receiving HBV vaccination, 6 (0.7%) were positive for anti‐HBc. Among them, one subject was suspected to have a possible subclinical HBV infection after the HBV vaccination. Conclusion : We report the current HBV vaccination‐related seroprevalence of anti‐HBs along with anti‐HBc in a Japanese tertiary medical institution consisting of more than 1000 HCP, which was an level comparable to similar sized hospitals in developed countries. Anti‐HBc would be important for understanding HBV status, but not necessary for general HBV vaccine management for HCP.